2018
DOI: 10.1080/01441647.2018.1559254
|View full text |Cite
|
Sign up to set email alerts
|

Firm-specific and location-specific drivers of business location and relocation decisions

Abstract: Decisions made by businesses on where to locate or relocate are typically given less consideration than residential location in integrated transport and land use modelling systems. This is surprising given the important role that businesses play in defining employment opportunities, and hence the travel patterns of workers and any travel associated with accessing firms. As part of a larger study on giving firm location choices an endogenous representation in an integrated model system, this paper reviews the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Arauzo-Carod et al (2010) identified a large number of factors, delineated in neoclassical and institutional, and emphasize increasing the quality of data in the relocation decision [13]. Balbontin & Hensher (2019) show that land use modeling and residential location in transport systems are not taken into account when locating or moving businesses [14]. Bodenmann & Axhausen (2012) propose several variables: production factors, economic environment, significance of municipal interventions.…”
Section: Research Organizationmentioning
confidence: 99%
“…Arauzo-Carod et al (2010) identified a large number of factors, delineated in neoclassical and institutional, and emphasize increasing the quality of data in the relocation decision [13]. Balbontin & Hensher (2019) show that land use modeling and residential location in transport systems are not taken into account when locating or moving businesses [14]. Bodenmann & Axhausen (2012) propose several variables: production factors, economic environment, significance of municipal interventions.…”
Section: Research Organizationmentioning
confidence: 99%
“…The considerations of location vary for each organization. Some of these considerations include seeking better accessibility for customers, availability of public transports, proximity to central business districts, better views, location capacity, attractive street settings and the need to centralize and decentralize business functions (Mazzarol and Choo, 2003; Kopczewska and Lewandowska, 2018; Balbontin and Hensher, 2019).…”
Section: The Pre-relocation Phasementioning
confidence: 99%
“…When organizations endeavor on implementing the relocation, various teams, managed by authoritative personnel (Rothe et al , 2014; Balbontin and Hensher, 2019), should be formed to collaboratively manage and implement the relocation activities and interactions (Mazzarol and Choo, 2003). These teams would be concerned with engaging employees, conducting location assessments, contractual leases and purchases, identifying and communicating workplace and employees' needs (NIST, 2013).…”
Section: The Pre-relocation Phasementioning
confidence: 99%
“…Initiate the pre-relocation activities (P1) Process definition. The "Initiate the pre-relocation activities" process (node "P1" in Figure 1) involves analyzing business needs (Balbontin and Hensher, 2019), assessment of the existing condition of facilities , assessment of relocation options (Christersson and Culley, 2018), planning for the relocation, allocating the budget needed for the relocation and designing the new premises. This process entails conducting meetings between the business managers and the facilities manager for reviewing the business needs, functional and technical workplace needs and the required workplace characteristics, as well as the legislative and regulatory workplace requirements.…”
Section: Generic Framework Model For Workplace Relocationmentioning
confidence: 99%
“…Analyze business needs for relocation (P1.1). This function will serve to inform the organization on its business needs (Balbontin and Hensher, 2019) for expansion and downsizing (Hills and Levy, 2014), centralization and decentralization (Lee, 2002), facilities requirements for mergers and acquisitions Christersson and Culley, 2018), need to terminate existing facilities and need to change region of operation. The activity starts by the identification of functional (Straub, 2009) and technical workplace Workplace relocation framework needs according to the organizational image and culture (Christersson and Rothe, 2012).…”
Section: Process Activitiesmentioning
confidence: 99%